Forbidden American English - Spears, Richard A. (Passport Books, 1990)
Containing approximately 1400 words and phrases that should not be used by educated speakers of English, this dictionary of offensive and often inflammatory vocabulary is designed to inform rather than to offend or entertain. --This text refers to an out of print or unavailable edition of this title.